MANAJEMEN PENGELOLAAN PORTAL BERITA WWW.GORIAU.COM DALAM MENARIK MINAT BACA PADA MEDIA SOSIAL - Azmi, Muhammad Faula; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Social media is now very popular among’s the people. Like the mass media, social media can also disseminate information to the public in general. One of social media is currently popular it’s news portals. This type of social media offer new information presented in the online form on a website. GoRiau.com is one of the leading news portal in Province of Riau. The further development of today's technology raises many new news portal. To competition, GoRiau.com through keredaksiannya face has a strategy to attract the requested read on social media. For this reason, this research is focused on the function of management on news portals GoRiau.com and what factors attract interest in reading to know.This research applies qualitative method with descriptive approach undertaken in GoRiau.com news portal, Sudirman streets No. 125 South Tangkerang, Bukitraya, Pekanbaru. Subjects of study include general chairman, chief editor, managing editor, and two journalists, as well as some of those readers who are determined through purposive method. Data collection techniques used were observation, interview, and documentation.The results of this study show that first, the management function in the editorial GoRiau.com news portal in an effort to attract interest in reading. GoRiau.com implement a planning that is done in three forms of the editorial meeting, which includes the planning meeting news content, placement planning meeting journalists, as well as evaluation. As for organizing, Goriau.com have determined the distribution of every reporter in accordance with the coverage of each post with the granting of work specified. Continue, regarding the actuating of the starting material coverage of news, collecting, writing, editing news on the website to which this form of utilization of new media. Form of controlling carried GoRiau.com one of which is the evaluation of the work, but other than that GoRiau.com also open a service complaint to the reader via e-mail. Second, the factors that attract interest in reading on this portal ie, interest, experience the same, and information needs. The entire series of the process is a form of editorial managerial done in order to attract readers.Keywords : Management, News Reading, Social Media